2019
DOI: 10.1186/s41240-019-0141-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sea mustard (Undaria pinnatifida) sporophylls from South Korea as fucoidan source and its corresponding antioxidant activities

Abstract: Sporophylls from sea mustard, Undaria pinnatifida, which are by-products in seaweed production industries, were taken from Hansan Island, Tongyeong, and Gijang, Busan, and investigated for their fucoidan content and corresponding antioxidant activities. The extracted fucoidan yield from sporophylls of sea mustard samples from Tongyeong (TF) and Gijang (GF) were 12.1% and 13.6%, respectively. The antioxidant activities assessment of TF and GF extracts showed relative significant difference between samples, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…The protein content was evaluated in another work by Neri et al (2019) using different samples from South Korea. The watersoluble protein values were consistent with those from this work [38]. The content of phloroglucinol was higher in this study compared with others.…”
Section: Liquid Fractions Propertiessupporting
confidence: 92%
See 1 more Smart Citation
“…The protein content was evaluated in another work by Neri et al (2019) using different samples from South Korea. The watersoluble protein values were consistent with those from this work [38]. The content of phloroglucinol was higher in this study compared with others.…”
Section: Liquid Fractions Propertiessupporting
confidence: 92%
“…The cell wall will be affected with more impact, to release high-value compounds from this raw material. Additionally, the valu HHV was evaluated, and we found a range of values from 16,665 to 22,803 kJ/kg present work, the values obtained for the residue of the brown seaweed were hi comparison to the values found for brown and red seaweeds, around 15,000-16,00 The water-soluble protein values were consistent with those from this work [38]. The content of phloroglucinol was higher in this study compared with others.…”
Section: Solid Residues Fractions Characterizationsupporting
confidence: 90%
“…A promising functional drink product from the brown seaweed Sargassum binderi tea contains fucoidan exhibits antioxidant activity [87]. Fucoidan from other species like wakame Undaria pinnatifida showed anticancer and antioxidant properties [88], anticoagulant [88], and antioxidant properties [89]. Generally, seaweed is known as a great source of some essential elements like iron and iodine [90].…”
Section: Nutraceuticals From the Algal And Cyanobacterial Originmentioning
confidence: 99%
“…This in concluded because of impurities present in the crude fucoidan extracted supported by protein present more than 0.1%. The studies show possible utilization of sea mustard sporophylls which are a byproduct in sea weed industry; as a source of fucodian for various applications in food industry [67]. Bushra et al reported that oxidative status in kidney tissue improvement and histological protectionagainst Cyclosporine A -induced kidney injury resulted due to fucodian.…”
Section: Yang Et Al Did a Comparative Study Between Pha Ie Pectin Hydroxamic Acids And Among Various Commercial Pectins With Different Dementioning
confidence: 99%